Diseño de un modelo multiobjetivo para la configuración de cadena de suministro inversa (2018)
This work has the objective of establishing the reverse logistics supply chain configuration taking into account environmental and economic variables through the formulation of a multi objective mixed integer programming model. The objectives of the problem studied were minimizing total cost and carbon dioxide emissions due to the network operation of expired medication in Barranquilla city. The set of solutions for the Pareto frontier was obtained through augmented epsilon constraint method, and the solution for implementation was determined through fuzzy logic rules. The model allowed integrating environmental and economic aspects, under uncertainty. In the same way, there was found an influence of the returned products in the network performance, specifically related to carbon dioxide emissions.